Two decades of Fomento ao Teatro for the city of São Paulo: the project as relevant materiality (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article investigates projects drawn up by theater groups to apply for public funding, a materiality that is present daily in today's theatrical activity. Its source of research is the 573 projects awarded by the first 40 editions of the Theater Promotion Program for the city of São Paulo. It briefly introduces the Program, and the research methodology based on a cartography of the awarded projects and then investigates the role of the selection committees and the groups' strategies for competing for the program's financial resources. Finally, it outlines the network of proposals made by the groups based on the examination and classification of the set of projects.
Keywords: project; public calls; collective theater; culture funding